Is Is English Considered Prestigious? Exploring Language Ideology Among University Students - Khoirin Nida Qurrota A'yun; Ila 'Iliyya; Reti Wahyuni, M.Pd. (English Journal Antartika, 2025)
In many higher education contexts, English holds a prestigious position, particularly in countries where it functions as a foreign language. Among university students, English is often associated with intelligence, academic competence, modern identity, and access to global opportunities. This study aims to explore how university students perceive English as a prestigious language and how this prestige ideology shapes their linguistic identity and confidence in academic and social contexts. This research employed a qualitative descriptive approach with a case study design. Five fifth-semester university students were selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis based on Braun and Clarke’s framework. The findings reveal that English functions as symbolic capital in university settings, influencing how students evaluate themselves and others. English prestige motivates students by providing access to academic and professional opportunities, such as scholarships, internships, and international programs. However, the findings also indicate that English prestige can generate pressure and anxiety, particularly for students who perceive their English proficiency as insufficient. Furthermore, English prestige significantly shapes students’ linguistic identity, producing both confidence and insecurity. To manage this tension, students actively negotiate their language use through adaptive strategies such as code-mixing to maintain inclusivity and self-confidence. This study highlights the dual role of English prestige as both empowering and constraining, emphasizing the importance of inclusive pedagogical practices that balance motivation with emotional support in English language learning.